Central Humanist Library at Faculty of Arts, University of Ljubljana: Yesterday – today – tomorrow?. Issue 1 (9th January 2017) - Vilar, Polona; Južnič, Primož
Abstract : Purpose: The purpose of this paper is to present a study of attitudes displayed towards the Central Humanist Library (CHL) from the perspective of both undergraduate and graduate students as well as librarians, specifically in light of the proposed relocation and merging of the library, which consists of 18 separate departments and is currently scattered across two locations. It is proposed that bringing all of the departments into a single building would enable a number of positive key changes, such as cost reduction (in terms of single premises), communication and cooperation between departments, as well as various other process and service improvements. Design/methodology/approach: A number of different techniques were employed to obtain and analyse various sets of data, depending on the target group: student responses were obtained through web surveys, focus groups and interviews, with data being extracted and analysed through descriptive analysis; librarians' responses were obtained through interviews, with data being extracted and an analysis driven through content analysis. Findings: The CHL has traditionally been a place with a lack of space and a focus on traditional library services (i.e. loan of printed materials). Other more technological aspects of library and information services are fulfilled by nearby resources, including public libraries and alternative university libraries. It is also worth noting that there is a stark difference in the perceptions of the CHL between students of the Social Sciences and the more traditional Humanities. Responses from librarians pointed towards the fact that many feel reluctant towards change. Research limitations/implications: As this study has only focused on three categories of end user, it should be noted that responses from faculty, researchers and doctoral students will be obtained in a separate research study, to enable a broader picture to be formed. Practical implications: As this research focused on the present library and current information needs of the students within different study programmes, planning should not be based on the present situation, but rather take account of future predictions and needs. It is suggested, therefore, that the following is also undertaken to assist future projects and provide further insight: informing students and librarians of findings; systematic weeding; and, as noted above, further investigation of other stakeholders, e.g. researchers, doctoral students, faculty and management. Originality/value: There is minimal information surrounding the attitudes of users and staff within the CHL – it is proposed that the findings of this study will assist in decisions regarding the renovation of newly acquired premises, and the subsequent relocation and reorganization of the existing library, staff, collections and services.